Rivas, Manuel (2023): "Lo que queda fuera". Pontevedra: Cuatro Lunas, 144 pp. - Roda Sánchez, Mar (Madrygal. Revista de Estudios Gallegos, 2023)
Review of Manuel Rivas’s Lo que queda fuera (Pontevedra, Cuatro Lunas, 2023) by Mar Roda Sánchez.